2020
DOI: 10.1186/s12966-020-00983-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of school meal nudge interventions to improve youth food behaviors

Abstract: Background: School meal programs have a large reach and thus are ideal environments in which to implement interventions targeting improved youth eating behaviors and reduced food waste. This systematic review summarizes the evidence on the effectiveness of school meal nudge interventions on influencing children's eating and waste behaviors. Methods: Inclusion criteria required studies have participants in primary or secondary school (grades K-12) with interventions that occurred during school lunch or breakfas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 57 publications
1
52
0
1
Order By: Relevance
“…Research has been conducted in laboratories (59,98,99) as well as online (33,71,72) . Critically, there is also a growing body of work conducted in real-world food settings (100) such as schools (101,102) , university cafeterias (103,104) , workplace (105) and healthcare sites (106) . To date, populations have included children and adolescents (101,102,107,108) , young adults at university (109) , adults (110) and older adults (74) .…”
Section: Choice Architecture Interventions To Nudge Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has been conducted in laboratories (59,98,99) as well as online (33,71,72) . Critically, there is also a growing body of work conducted in real-world food settings (100) such as schools (101,102) , university cafeterias (103,104) , workplace (105) and healthcare sites (106) . To date, populations have included children and adolescents (101,102,107,108) , young adults at university (109) , adults (110) and older adults (74) .…”
Section: Choice Architecture Interventions To Nudge Populationsmentioning
confidence: 99%
“…Critically, there is also a growing body of work conducted in real-world food settings (100) such as schools (101,102) , university cafeterias (103,104) , workplace (105) and healthcare sites (106) . To date, populations have included children and adolescents (101,102,107,108) , young adults at university (109) , adults (110) and older adults (74) . Similar effects in adults and children have been reported (100) and a systematic review (108) examining children's dietary behaviour and nudge interventions found positive results in thirty-three of the forty studies.…”
Section: Choice Architecture Interventions To Nudge Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…interventions 57 are also frequently implemented in school nutrition programs to improve dietary behaviors and reduce food waste. 58 Yet, there are few peer-reviewed studies that evaluate the impact of these interventions on waste, and the limited available evidence suggests that behavioral economics interventions are associated with no change in or increased levels of waste. 58 For example, researchers increased the portion size of the fruits and vegetables during school lunch by 50% in an effort to improve fruit and vegetable consumption.…”
Section: Homementioning
confidence: 99%
“…58 Yet, there are few peer-reviewed studies that evaluate the impact of these interventions on waste, and the limited available evidence suggests that behavioral economics interventions are associated with no change in or increased levels of waste. 58 For example, researchers increased the portion size of the fruits and vegetables during school lunch by 50% in an effort to improve fruit and vegetable consumption. Although consumption increased for the items that were served in larger portions, there were also increases in fruit and vegetable waste.…”
Section: Homementioning
confidence: 99%